Divergent synthesis of oxepino-phthalides and [5,5]-oxaspirolactones through [2+2+2]- and [2+3]-annulation of alkynyl alcohols with a-ynone-esters - Kambale, Digambar A.; Borade, Balasaheb R.; Vinodkumar, Ramavath; Kontham, Ravindar (Journal of Organic Chemistry, 2023)
Unmasking the synthetic potential of alkyne functional group of alkynyl alcohols as surrogates of carbonyl compounds, herein we present the first Bronsted acid (TfOH)-catalyzed [2 + 2 + 2]-annulation of 4-pentyn-1-ols (possessing terminal alkyne) with a-ynone-esters to access tricyclic tetrahydro-oxepino-phthalides. Besides, an unprecedented synthesis of a-acetoaryl or a-alkynyl [5,5]-oxaspirolactones has been demonstrated by employing 4-pentyn-1-ols (possessing an internal alkyne) as an annulation partner, which proceeds through a divergent [2 + 3]-annulation pathway.

Bronsted acid-promoted cyclodimerization of α,β-unsaturated γ-ketoesters: construction of fused pyrano-ketal-lactones and γ-ylidene-butenolides - Vinodkumar, Ramavath; Nakate, Ashwini K.; Sharma, Himanshu; Vanka, Kumar; Rama Krishna, Gamidi; Kontham, Ravindar (ACS Omega, 2024)
Unprecedented MsOH-promoted diastereoselective cascade dimerization and intramolecular lactonization of readily accessible alpha,beta-unsaturated gamma-ketoesters are presented. The results obtained in this work, control experiments, and density functional theory (DFT) calculations suggested that the initial enolization and E to Z isomerization/equilibration of olefin (C=C) of substrate alpha,beta-unsaturated gamma-ketoesters give a Z-isomer preferentially over an E-isomer. Subsequently, the Z-isomer undergoes intermolecular annulation with alpha,beta-unsaturated gamma-ketoesters via domino Michael addition/ketalization/lactonization steps to furnish fused tetracyclic pyrano-ketal-lactone. However, the Z-isomer prefers intramolecular trans-esterification in a competing pathway and gives bicyclic gamma-ylidene-butenolide. The key features of this work include simple Br & oslash;nsted acid catalysis, the formation of three bonds, two rings, and three contiguous stereogenic centers in a single step, DFT calculations, and the assignment of relative stereochemistry through X-ray diffraction (XRD) and two-dimensional (2D) nuclear magnetic resonance (NMR) analyses.

Ready access to [5,6,5]-Trioxa-spiro and fused ketals via ag-catalyzed cascade annulation of 4-pentyn-1-ols and aldehydes - Vinodkumar, Ramavath; Nakate, Ashwini K.; Gamidi, Rama Krishna; Kontham, Ravindar (Organic Letters, 2024)
In this study, we unveil the versatility of 4-pentyn-1-ols as carbonyl surrogates for the unprecedented synthesis of diverse oxygen heterocycles, including [5,6,5]-bis-spiroketals (trioxadispiroketals) and [5,6,5]-furano-spiroketals related to bioactive natural products. These reactions commence with the pi-activation-induced intramolecular hydroalkoxylation of 4-pentyn-1-ols, yielding cyclic enol ethers, which undergo subsequent three-component annulation with aldehydes in a [2+2+1+1] fashion, resulting in the formation of [5,6,5]-bis-spiroketals. Notably, the distinctive steric features of alkynyl alcohols, particularly those with a secondary or tertiary alcohol functionality, dictate divergent reaction pathways, leading to the formation of [5,6,5]-furano-spiroketals.

AgOTf-catalyzed cascade annulation of 5-hexyn-1-ols and aldehydes: enabling the diastereoselective synthesis of [6,6,6]-trioxa-fused ketals and hexahydro-2H-chromenes - Vinodkumar, Ramavath; Nakate, Ashwini K.; Krishna, Gamidi Rama; Kontham, Ravindar (Chemical Communications, 2025)
We report the unprecedented diastereoselective synthesis of novel [6,6,6]-trioxa-fused ketals via AgOTf-catalyzed cascade annulation of 5-hexyn-1-ols (with primary or secondary hydroxyl groups) and aldehydes through a [2+2+1+1] pathway. In contrast, 5-hexyn-1-ols with tertiary hydroxyl groups yield hexahydro-2H-chromenes via a [3+1+1+1] pathway.

The first enantioselective total synthesis of the eremophilane-type sesquiterpenoid (-)-peniroqueforin C - Ingale, Sudhir R.; Vinodkumar, Ramavath; Kontham, Ravindar (Tetrahedron Letters, 2025)
Herein, we report the first stereoselective total synthesis of the eremophilane-type sesquiterpenoid (-)-peniroqueforin C using a chiral-pool strategy. This synthetic route features the use of readily available (S)-(+)-carvone as a chiral building block, Robinson annulation to construct the decalin system, substrate-controlled stereoselective methylation, single-step annulative construction of a tricyclic gamma-ylidene-butenolide with concomitant alkene transposition, and direct lactone-to-lactam conversion as key transformations.
Keywords: annulation reactions; Eremophilanes; Peniroqueforin C; Sesquiterpenoids; Total synthesis